2011
DOI: 10.1111/j.1521-0391.2011.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Memory Impairment Associated with Discrepancies between Retrospective and Daily Recall of Alcohol Consumption

Abstract: Prior studies have found discrepancies between daily report and retrospective recall of alcohol use. One possible explanation is that there may be an association between memory impairment and alcohol consumption recall errors. Should this possibility be substantiated it could have implications for the types of assessments conducted in alcohol treatment trials. The current study evaluated the degree to which memory impairment, as measured by the California Verbal Learning Test-II, predicted day-to-day discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…, we also found that men's degree of correspondence increased for all of the drinking indices over the 5 weeks, and most notably for standard drinks. Given that findings indicated greater discrepancies for men even after controlling for total drinks, it is possible that long‐term effects of heavier drinking, such as memory impairment, are contributing to these gender differences, though data were not available regarding the duration of individuals’ heavy drinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, we also found that men's degree of correspondence increased for all of the drinking indices over the 5 weeks, and most notably for standard drinks. Given that findings indicated greater discrepancies for men even after controlling for total drinks, it is possible that long‐term effects of heavier drinking, such as memory impairment, are contributing to these gender differences, though data were not available regarding the duration of individuals’ heavy drinking.…”
Section: Discussionmentioning
confidence: 99%
“…This study also extends previous research suggesting that individuals who drink more tend to produce greater discrepancies between retrospective recall and daily monitoring, and provides preliminary evidence that gender may also explain between‐person variability in the degree of correspondence. As such, future research should continue to assess other moderating variables, such as memory impairment, clinical comorbidities, and other individual difference factors that may influence degree of correspondence.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 That is, patients typically underestimate the amount of alcohol they have used and the duration of their alcohol addiction, and they also misjudge the severe and adverse consequences of alcohol addiction on daily life and health functioning. 13 15 Impaired illness insight can be regarded as a continuum ranging from total denial of the disease to more subtle metacognitive awareness deficits. 11 Illness insight comprises of awareness of illness, the capacity to view symptoms of the disease as pathological, and treatment adherence.…”
Section: Introductionmentioning
confidence: 99%
“… 26 29 Moreover, these alcohol-related cognitive deficits can affect the results of self-report questionnaires in such a way that it can lead to clinical misinterpretation. 13 , 30 32 In order to avoid this misinterpretation of alcohol-related cognitive deficits, the combined use of self-reported information and information reported by informants who know the patient very well is essential for adequate diagnosis and in particular for the assessment of impaired self-awareness.…”
Section: Introductionmentioning
confidence: 99%
“…That cognitive dysfunctions can influence self‐report is also shown in a recent study with alcohol‐dependent patients by Lincoln et al . [74]. They found impairments in the estimation and self‐evaluation of past alcohol intake that could be attributed to verbal memory dysfunctions contingent upon chronic alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%